Working Environment Activities in Hospitals: Expansion of Scope and Decentralization of Responsibility - Borgen, Per-Christian; Lunde, Bente Vibecke (Nordic Journal of Working Life Studies, 2021)
This article analyzes how two development traits in the regulatory requirements for Working Environment (WE) activities – an expansion of scope and a decentralization of responsibility – are understood and handled over time by actors responsible for WE activities in Norwegian hospitals. The expanded scope of WE activities is studied based on the requirements outlined in The Working Environment Act, public health science theory, and the WE challenges in hospitals. The decentralized responsibility for WE activities is studied based on Internal Control (IC) reform and other hospital reforms inspired by New Public Management (NPM). The final section of the article discusses the effects of the two development traits, and how these enlarge the line manager’s area of responsibility. The article is based on a qualitative, longitudinal study conducted in three Norwegian hospitals in 1998-1999 and 2013.